2003
DOI: 10.1002/macp.200390028
|View full text |Cite
|
Sign up to set email alerts
|

Early Stages of Propylene Bulk Phase Polymerization with Supported Metallocene Catalysts

Abstract: For the initial steps of propylene bulk phase polymerization with a silica‐supported metallocene/MAO‐catalyst the processes of polymer growth, particle expansion and carrier fragmentation are investigated. Gravimetric analysis of the kinetics is given. Light optical examination of the particles shows a significant particle expansion during the first minutes of polymerization, which is not comparable to known observation from the slurry process. Electron microscopic investigation on cross sections of the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
53
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 14 publications
(23 reference statements)
3
53
0
1
Order By: Relevance
“…More recently, Olalla et al [25] improved the original gas-phase short-stop technique [5,26] in order to study heat transfer in gas-phase olefin polymerization on supported catalyst; they found that the rate of reaction has a very strong influence on the rate of fragmentation and also showed that the shape of the rate curve is dependent on the initial conditions of the polymerization, suggesting that the mechanism of fragmentation of the catalyst carrier depends on the start-up of the polymerization. The latter observation confirmed an earlier result of Knocke et al [27] These and other articles in a similar vein all point to the fact that fragmentation influences the morphology, but that the rate of polymerization during the fragmentation step and the physical properties of the polymer present during this stage all interact in a complex manner. Tools for the study of these aspects of olefin polymerization on supported catalysts are therefore extremely useful.…”
Section: Introductionsupporting
confidence: 88%
“…More recently, Olalla et al [25] improved the original gas-phase short-stop technique [5,26] in order to study heat transfer in gas-phase olefin polymerization on supported catalyst; they found that the rate of reaction has a very strong influence on the rate of fragmentation and also showed that the shape of the rate curve is dependent on the initial conditions of the polymerization, suggesting that the mechanism of fragmentation of the catalyst carrier depends on the start-up of the polymerization. The latter observation confirmed an earlier result of Knocke et al [27] These and other articles in a similar vein all point to the fact that fragmentation influences the morphology, but that the rate of polymerization during the fragmentation step and the physical properties of the polymer present during this stage all interact in a complex manner. Tools for the study of these aspects of olefin polymerization on supported catalysts are therefore extremely useful.…”
Section: Introductionsupporting
confidence: 88%
“…The detailed study of such phenomena as the pore clogging with polymer, the transport in the evolving 3-D pore phase of catalyst/polymer particle, and the fragmentation of the porous catalyst carrier is the subject of ongoing research in our group. Experimental study of the fragmentation process at very slow polymerization rates was carried out by Pater et al 18 and Knoke et al, 19 who stressed the importance of the rate of polymer formation inside the pores of the support.…”
Section: Introductionmentioning
confidence: 99%
“…These latter experiments can be subdivided into two groups: (i) very controlled conditions (low T, P) to get low reaction rates. [8] This has the obvious disadvantage of producing particles in a manner different from that in a real process; (ii) idealised supports (e.g. silica wafers).…”
Section: Introductionmentioning
confidence: 99%
“…However, if one examines the curves for the ''mild'' runs, it is clear that after a short time, there is a ''plateau'' that lasts for approximately 5 to 6 seconds, and then the reaction begins to accelerate once again. The most likely explanation for this plateau is the one offered by Knocke et al [8] . These authors investigated polymerisation on silica-supported metallocenes, and saw plateaux much like the ones in Figure 5 under the vapour pressure of liquid propylene at 50 8C.…”
mentioning
confidence: 97%